O Serviço Integrado de Atendimento ao Trauma em Emergência (SIATE) como fonte de informações de acidentes de trabalho em Londrina, PR - Baldo, Renata Cristina Silva; Spagnuolo, Regina Stella [UNESP]; Almeida, Ildeberto Muniz De [UNESP] (Fundação Jorge Duprat Figueiredo de Segurança e Medicina do Trabalho - FUNDACENTRO, 2015)
Objective: to describe the occupational accidents characteristics and the profile of their victims assisted by the Emergency Trauma Care Integrated Service (SIATE) in Londrina, PR, Brazil. Methods: a descriptive cross-sectional study; data was collected from July 1st to December 31st, 2008, through telephone interviews with the victims or their relatives. Additional information was collected from SIATE rescuers’ reports. Results: 1,312 interviews were performed and 465 (35.4%) cases were considered occupational accidents. The predominant profile of such victims was of a young male legally employed. Most occupational accidents occurred in the street, and 376 (80.9%) were traffic-related. Of those, approximately 65.0% were identified as occupational route accidents. None of the identified cases had been reported to the Ministry of Health Information System. The Social Security system shows 40.0% underreporting involving formal workers accidents. Conclusion: occupational health services should prioritize prevention actions on accidents occurred in the streets, as well as implement systematic routines aiming at enhancing the reporting of these cases in databases of national interest, in accordance with the Ministry of Health.

Objetivo: descrever as características dos acidentes de trabalho e o perfil das vítimas atendidas pelo Serviço Integrado de Atendimento ao Trauma em Emergência, de Londrina (SIATE), PR. Métodos: trata-se de estudo descritivo transversal. Os dados foram coletados no período de 1º julho a 31 de dezembro de 2008, por meio de entrevistas telefônicas às vítimas ou familiares e busca de informações complementares em relatórios de atendimento dos socorristas. Resultados: foram realizadas 1.312 entrevistas, sendo 465 (35,4%) casos considerados acidentes de trabalho. O perfil predominante dos acidentados é jovem, do sexo masculino, inserido no mercado formal de trabalho como empregado. A maioria dos acidentes de trabalho ocorreu na rua, sendo 376 (80,9%) relacionados ao trânsito; desses, cerca de 65,0% foram identificados como acidentes de trajeto. Nenhum dos casos foi notificado em sistema de informação do Ministério da Saúde. Junto à Previdência Social houve subnotificação de cerca de 40% dos casos de acidentes ocorridos com trabalhadores formais. Conclusão: os serviços de Saúde do Trabalhador devem priorizar ações de prevenção de acidentes ocorridos no espaço da rua, assim como implantar rotinas sistematizadas a fim de intensificar a notificação dos casos em bancos de dados de interesse nacional, conforme preconiza o Ministério da Saúde.
The Emergency Trauma Care Integrated Service (SIATE) as a source of information on occupational accidents in Londrina, PR, Brazil
Keywords: occupational accidents; workers’ health; traffic accidents; route accidents; underreporting; acidentes de trabalho; saúde do trabalhador; acidentes de trânsito; acidentes de trajeto; subnotificação